Responses of quinoa (Chenopodium quinoa Willd.) seeds stored under different germination temperatures - Andressa Strenske; Edmar Soares de Vasconcelos; Vanessa Aline Egewarth; Neusa Francisca Michelon Herzog; Marlene de Matos Malavasi (Acta Scientiarum. Agronomy, 2017)
In this experiment, we assessed the germination and vigor of quinoa seeds packed in paper bags and stored at room temperature for 36, 85, 119, 146, 177 and 270 days. The seeds were harvested under experimental conditions in Marechal Candido Rondon, Paraná, during the 2012/13 growing seasons. Four replicates of 100 seeds each were established for each storage time, and the seeds were evaluated, on paper, based on the BOD under the following experimental temperature conditions: alternating temperatures of 20 and 30°C and a constant temperature of 25°C. The seeds from both treatments were subject to seven-hour photoperiods and 25°C under continuous darkness. The germinated seeds were counted daily for eight days after sowing, and we evaluated the percentages of normal and abnormal seedlings and the germination index. The experimental design was completely randomized using a split-plot design. Increasing the storage time decreased the percentage of germinated seeds and seed vigor due to the increased number of abnormal seedlings. Over the 430-day study period, quinoa seed germination completely declined under the experimental conditions. The final number of germinating seeds should be evaluated 7 days after the beginning of the germination test.